Application of The Pentahelix Concept in The Iconic Tourism Destination of Kampung Ketupat Samarinda, Indonesia - Habibi, Muhammad; Yani, Ahmad; Eryani, Trisna Waty Riza (Golden Ratio of Social Science and Education, 2025)
Samarinda continues to develop towards its vision as a "city center of civilization." One key effort in strengthening its tourism sector is Kampung Ketupat Samarinda Seberang, an iconic destination that blends Banjar and Bugis cultures. This study employs a qualitative exploratory approach to analyze the role of the Pentahelix elements—government, academia, community, media, and business—in shaping tourism policies for Kampung Ketupat. The analysis follows the interactive model by Miles, Huberman, and Saldana (2014), consisting of data condensation, data display, and conclusion drawing and verification. The government plays a crucial role in transforming Kampung Ketupat from a small home-based business into a leading tourist destination in Samarinda, officially recognized with a tourism award in 2023. Academics, including lecturers and researchers, contribute through the Community-Based Tourism (CBT) concept, implemented by Pokdarwis and residents, along with the "Kotaku" program from the Samarinda City Government. Strategic collaboration was strengthened by the visit of the Deputy Chairperson of Commission X of the Indonesian House of Representatives and the Director of Regional Destination Development II from the Ministry of Tourism and Creative Economy. This facilitated synergy between the East Kalimantan Provincial Tourism Office, the Samarinda City Tourism, Youth, and Sports Office, travel agencies, the Indonesian Tour Guide Association (HPI), and the Samarinda CSR Forum. Both mass media and social media play a vital role in promoting Kampung Ketupat, enhancing its appeal as a cultural and economic tourism destination. With the collective support of all Pentahelix elements, Kampung Ketupat continues to grow as a sustainable tourism icon in Samarinda.